THE EFFECT OF JOB SATISFACTION, ORGANIZATIONAL CULTURE AND WORK STRESS ON ORGANIZATIONAL COMMITMENT TO CIVIL SERVANTS AT THE REGIONAL SECRETARIAT OF PEMALANG REGENCY - Fatmah Bagis; Lana Dianti; Akhmad Darmawan; Dwi Vina Rahmawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to analyse the effect of job satisfaction, organizational culture and work stress on organizational commitment to civil servants at the regional secretariat of Pemalang Regency. The population in this study were all Civil Servants of the Pemalang Regency Regional Secretariat, as many as 170 employees. The sampling in this study used the nonprobability sampling method with the incidental sampling technique with a sample of 100 respondents. Data obtained from respondents with research instruments using questionnaires. Technique of analysis in this research used Partial Least Square (PLS). Based on the research showed job satisfaction, organizational culture and work stress have a significant positive effect on organizational commitment. The research shows that job satisfaction variable has a significant positive effect on organizational commitment. The showed that organizational culture variable has no significant effect on organizational commitment. The results also show the work stress had significant effect on organizational commitment. Keywords: Organizational commitment, job satisfaction, organizational culture, work stress